COGNITIVE ASPECTS OF ENGLISH PHRASAL VERBS IN LITERARY TEXTS: Gulmurodova Gulzoda, Tukhtakhodjayeva Z. T. - 1st year, MA Department, Gulmurodova Gulzoda; UzSWLU Sc. Advisor, Tukhtakhodjayeva Z. T. PhD, As. Prof (Лучшие интеллектуальные исследования, 2024)
This article is devoted to the cognitive features of phrasal verbs in literary texts in English and it investigates how phrasal verbs are encoded, accessed, and interpreted in human mind. The phrasal verbs in literary works such as “1984” by George Orwell and “Rich Dad and Poor Dad” by Robert Kiyosaki will be analyzed, in particular. Furthermore, conceptual metaphor analysis will be conducted to analyze how phrasal verbs are utilized in the text.